2016
DOI: 10.1007/s40273-016-0481-1
|View full text |Cite
|
Sign up to set email alerts
|

Degarelix for Treating Advanced Hormone-Dependent Prostate Cancer: An Evidence Review Group Perspective of a NICE Single Technology Appraisal

Abstract: As part of its Single Technology Appraisal Process, the National Institute for Health and Care Excellence (NICE) invited the manufacturer of degarelix (Ferring Pharmaceuticals) to submit evidence for the clinical and costeffectiveness of degarelix for the treatment of advanced hormone-dependent prostate cancer. The School of Health and Related Research Technology Appraisal Group at the University of Sheffield was commissioned to act as the independent Evidence Review Group (ERG). The ERG produced a critical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 10 publications
1
9
0
3
Order By: Relevance
“…Diese Tendenz spiegelt sich auch in einer anderen direkten Vergleichsstudie mit 284 Patienten wider: Die 9-Monats-Überlebensrate war für Triptorelin signifikant höher als für Leuprorelin (97,0 % vs. 90,5 %; p = 0,033) [29]. Auch eine Netzwerkanalyse von Uttley et al zeigte eine niedrigere Mortalität unter Triptorelin im Vergleich zu Degarelix [30].…”
Section: Diskussionunclassified
“…Diese Tendenz spiegelt sich auch in einer anderen direkten Vergleichsstudie mit 284 Patienten wider: Die 9-Monats-Überlebensrate war für Triptorelin signifikant höher als für Leuprorelin (97,0 % vs. 90,5 %; p = 0,033) [29]. Auch eine Netzwerkanalyse von Uttley et al zeigte eine niedrigere Mortalität unter Triptorelin im Vergleich zu Degarelix [30].…”
Section: Diskussionunclassified
“…14 Incluso se discute la metodología empleada en varios de los trabajos que establecen la asociación. 5 Entre ellos, un metanálisis publicado en JAMA, no logró demostrar la asociación entre el uso de los agonistas de la GnRh y la mortalidad cardiovascular. 12 Esos hallazgos hacen que la evidencia sea contradictoria.…”
Section: 25%unclassified
“…4 De igual manera, se encuentra evidencia contradictoria entre el uso de agonistas de la GnRh específicamente y el aumento de eventos cardiovasculares. 5 Todo ello ha conducido a que diversas sociedades científicas elaboren recomendaciones sobre la necesidad de valorar el incremento del riesgo que se produce en esas circunstancias. 6 El objetivo principal de este estudio es determinar la prevalencia de eventos cardiocerebrovasculares en pacientes con cáncer de próstata que son tratados con bloqueo androgénico con agonistas de la GNRH.…”
Section: Introductionunclassified
“…A technology appraisal commissioned by the National Institute for Health Care and Excellence (NICE) in the UK reviewed the evidence supporting the use of the GnRH antagonist degarelix for the treatment of advanced prostate cancer and selected leuprolide, goserelin, and triptorelin as comparators [ 61 ]. A mixed treatment comparison meta-analysis of a total of six studies of the selected agents revealed that leuprolide and goserelin were associated with increased mortality compared with degarelix (odds ratio [OR] 1.8 and 1.9, respectively).…”
Section: Are All Adts the Same?mentioning
confidence: 99%
“…A mixed treatment comparison meta-analysis of a total of six studies of the selected agents revealed that leuprolide and goserelin were associated with increased mortality compared with degarelix (odds ratio [OR] 1.8 and 1.9, respectively). In contrast, mortality with triptorelin was lower than with degarelix (OR 0.5), leading the NICE Evidence Review Group to consider that the treatment effect of triptorelin on overall survival may differ from that of leuprolide and goserelin [ 61 ]. While this analysis is intriguing, more large-scale head-to-head comparisons would be needed to draw firm conclusions on the effects of different ADTs on survival.…”
Section: Are All Adts the Same?mentioning
confidence: 99%